EVALUATION OF DRUG THERAPY IN PROGRESSING DIFFERENTIATED THYROID CANCER REFRACTORY TO RADIOACTIVE IODINE IN PATIENTS RESIDING IN THE RUSSIAN FEDERATION : PHARMACOECONOMIC ASPECTS - M. Yu. Frolov; V. A. Rogov (Фармакоэкономика)
The aim of this study was to identify the most effective (in the clinical and pharmacoeconomic aspects) drug for the treatment of widespread progressing differentiated thyroid cancer (DTC) refractory to radioactive iodine in patients – residents of the Russian Federation.Materials and Methods. The budget impact and the “cost-effectiveness” parameters were analyzed using the MS Excel-model based on a 3-year period. The “cost-effectiveness” analysis was performed to compare the use of lenvatinib 15.28 mg/day, sorafenib 651 mg/day (after dose reduction), and chemotherapeutic agents. As part of the budget impact analysis (BIA), two scenarios were simulated: 1. DTC treatment using sorafenib and the chemotherapeutic agents (CTA);2. In some patients, the sorafenib + CTA therapy has been replaced with lenvatinib. The only parameter analyzed in this model was the drug cost. In the BIA, the impact of scenario 2 on the entire budget reserved for the thyroid cancer treatment was evaluated.Results. Lenvatinib proved an effective agent (with a manageable safety profile) to be used in monotherapy of DTC refractory to radioactive iodine. According to the BIA, the introduction of lenvatinib had virtually no effect on the cost of thyroid cancer treatment. Using the “progression free survival” parameter, the cost-effectiveness ratio (CER) showed that the annual cost of effective treatment of DTC refractive to radioactive iodine with sorafenib or lenvatinib was 7 285 716.92 rubles or 3 368 077.62 rubles, respectively.